Penambahan Air Laut, Inokulasi Rhizobium Terhadap Kadar Protein Kasar Dan Fermentabilitas Jerami Kedelai In Vitro - Asmaul Husna; Surahmanto Surahmanto; Eny Fuskhah (Universitas Muhammadiyah Purworejo, 2016)
This study aims to determine the levels of crude protein (PK), ammonia (NH3) and volatile fatty acid (VFA) of soybean straw with the addition of seawater and Rhizobium bacteria. The research was conducted in 3 stages, namely the preparation, preliminary and treatment stages. The experimental design used was a completely randomized design (CRD) 4 x 2 factorial pattern with 4 replications. The first factor is seawater with treatment (L0, L1, L2 and L3), namely without seawater, dilution of seawater is 1 mmhos / cm, dilution of seawater is 2 mmhos / cm and dilution of seawater is 3 mmhos / cm. The second factor was Rhizobium bacteria treated (R1 and R2) without Rhizobium bacteria and the addition of Rhizobium bacteria, respectively. The parameters observed included levels of PK, NH3 and VFA. PK laboratory analysis was measured by the Kjeldahl method, for NH3 production was measured by the Conway microdilution method and VFA production was measured by steam distillation techniques. The data obtained were analyzed based on analysis of variance, and if the treatment had a significant effect, it was continued with the Duncan multiple area test at 5% level to test the differences between each treatment. The results showed that the use of seawater and Rhizobium bacteria had no significant effect on PK levels, NH3 production and had a significant effect on VFA production with the given seawater treatment. The average PK levels in the L0, L1, L2 and L3 treatments were 10.35; 10,13; 9.32 and 9.68% the average value of NH3 production is 4.26; 4.16; 4.09 and 4.14 mM, while the average VFA production was 112; 113; 92 and 127 mM.